PENGAPLIKASIAN KALENDER JADWAL POSYANDU BAGI IBU YANG MEMILIKI BALITA DI DESA SIKKUALE KECAMATAN CEMPA KABUPATEN PINRANG - Kamariana, Kamariana; Ridjal, Andi Tilka Muftiah (Jurnal BALIRESO, 2018)
Posyandu is a community-based health service especially for infants, toddlers and pregnantwomen. There are several factors that affect the routine of mother visits to posyandu, such aseducation and knowledge. This activity aimed to assist mothers in obtaining information aboutweighing schedule of under-five-children by applying posyandu calendar. The results revealed thatmothers visiting posyandu were regularly preferable to join posyandu weighing program.